Factors Associated with the Delay of Early Initiation of Breastfeeding in Hospitals: A Scoping Review - Suminar, Dian Laras; Bachtiar, Adang; Mulyana, Nana (LPPM Universitas Respati Indonesia, 2024)
Background: Early Initiation of Breastfeeding (EIB) is a crucial practice that supports newborn health and the success of exclusive breastfeeding. Despite its known benefits, the implementation of EIB faces several challenges, particularly in hospital settings. Objective: This scoping review aims to identify and map the factors that delay EIB in hospitals, providing insight into the barriers that hinder its effective practice. Method: A comprehensive search was conducted across four databases—Google Scholar, Semantic Scholar, Elsevier, and PubMed—using terms related to EIB obstacles. Results: Initially, 1,276 articles were identified, and after applying the PRISMA method for screening, 14 articles were included in final analysis. The review highlights several obstacles to EIB, including cognitive factors like mothers’ lack of knowledge and experience, operational challenges such as high workloads and limited resources among health staff, and postpartum factors, particularly discomfort following cesarean sections. These issues were found to be consistent across various settings. Conclusions: To address these barriers, the review emphasizes the need for improved education for mothers and healthcare providers, stronger hospital policies supporting EIB, and better resource availability, such as counseling materials. Implementing these strategies is vital for optimizing EIB practices and achieving better health outcomes for mothers and newborns while supporting global breastfeeding initiatives. Keywords: Delay, early initiation of breastfeeding (EIB), Hospital